2019
DOI: 10.1007/s12187-019-9626-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Poverty and Children’s General Health at 8 Years of Age in the Taiwan Birth Cohort Study

Abstract: There are growing concerns about the effects of poverty on children's health, but few studies have examined how the long-term experience of poverty affects the general health of children. We sought to investigate the relationship between children's poverty experience from birth to school age and their general health status. Data from the Taiwan Birth Cohort Study (TBCS), a nationally representative sample of 17,853 children born in 2005 were used. Mother-rated health of children at age 8 was assessed. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…5 6 Empirical studies have demonstrated that poor children have a higher risk of experiencing adverse health outcomes and death than their less impoverished peers. [7][8][9][10][11] Health conditions during the crucial early childhood period shape lifelong health. 12 Since the Barker hypothesis was first introduced in the 1990s, the long-term effects of early developmental experiences on health and disease risk into adulthood have been recognised and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…5 6 Empirical studies have demonstrated that poor children have a higher risk of experiencing adverse health outcomes and death than their less impoverished peers. [7][8][9][10][11] Health conditions during the crucial early childhood period shape lifelong health. 12 Since the Barker hypothesis was first introduced in the 1990s, the long-term effects of early developmental experiences on health and disease risk into adulthood have been recognised and investigated.…”
Section: Introductionmentioning
confidence: 99%